Nicotine up-regulates α4β2 nicotinic receptors and ER exit sites via stoichiometry-dependent chaperoning - Srinivasan, Rahul (The Rockefeller University Press, 2011)
The up-regulation of α4β2* nicotinic acetylcholine receptors (nAChRs) by chronic nicotine is a cell-delimited process and may be necessary and sufficient for the initial events of nicotine dependence. Clinical literature documents an inverse relationship between a person’s history of tobacco use and his or her susceptibility to Parkinson’s disease; this may also result from up-regulation. This study visualizes and quantifies the subcellular mechanisms involved in nicotine-induced nAChR up-regulation by using transfected fluorescent protein (FP)-tagged α4 nAChR subunits and an FP-tagged Sec24D endoplasmic reticulum (ER) exit site marker. Total internal reflection fluorescence microscopy shows that nicotine (0.1 µM for 48 h) up-regulates α4β2 nAChRs at the plasma membrane (PM), despite increasing the fraction of α4β2 nAChRs that remain in near-PM ER. Pixel-resolved normalized Förster resonance energy transfer microscopy between α4-FP subunits shows that nicotine stabilizes the (α4)(2)(β2)(3) stoichiometry before the nAChRs reach the trans-Golgi apparatus. Nicotine also induces the formation of additional ER exit sites (ERES). To aid in the mechanistic analysis of these phenomena, we generated a β2(enhanced-ER-export) mutant subunit that mimics two regions of the β4 subunit sequence: the presence of an ER export motif and the absence of an ER retention/retrieval motif. The α4β2(enhanced-ER-export) nAChR resembles nicotine-exposed nAChRs with regard to stoichiometry, intracellular mobility, ERES enhancement, and PM localization. Nicotine produces only small additional PM up-regulation of α4β2(enhanced-ER-export) receptors. The experimental data are simulated with a model incorporating two mechanisms: (1) nicotine acts as a stabilizing pharmacological chaperone for nascent α4β2 nAChRs in the ER, eventually increasing PM receptors despite a bottleneck(s) in ER export; and (2) removal of the bottleneck (e.g., by expression of the β2(enhanced-ER-export) subunit) is sufficient to increase PM nAChR numbers, even without nicotine. The data also suggest that pharmacological chaperoning of nAChRs by nicotine can alter the physiology of ER processes.